ANALISIS WACANA DALAM FENOMENA WORKAHOLISM PADA KARYAWAN PT. KUSUMA MULIA TEXTILE - Kurniawati, Aisyah; Nurhadi, Nurhadi (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The phenomenon of workaholism has occurred a lot in society, so it is important to carry out an in-depth analysis to examine this phenomenon. The focus of this research is to examine the phenomenon of workaholism using the lens of Foucault's discourse analysis theory with two methodologies used, namely archeology of knowledge and genealogy of power. The aim of this research is to reveal the discourse of workaholism that occurs among PT. Kusuma Mulia Textile workers. This research approach is qualitative research using the case study method. The data comes from documentation, interviews and direct observation using purposive sampling techniques. The results of the analysis, there are values that power wants to build, namely creating a comfortable working atmosphere, establishing flexible working hours at certain position levels, and related work contract agreements. Internalization of values is carried out through company regulations, leadership policies, and instilled habits. This discourse aims to form workers who are loyal, responsible and make maximum contributions to company. The regulation produce knowledge and become truth to workers. So as to produce employees who are disciplined and obedient. This discipline is considered to be the most effective method and mechanism in instilling discourse and exercising domination.